Reconciling public administration and democracy: the role of the responsible administrator - Burke, John P. (1997)
This article considers whether the individual responsibilities of bureaucratic officials provide a useful means for reconciling the tension between democracy and bureaucracy. Three questions central to the proper definition of bureaucratic responsibility are examined: (1) What is the relation of bureaucratic responsibility to the view that proper bureaucratic conduct is essentially a matter of ethics and morality? (2) If the appeal to moral values does not ordinarily offer an acceptable guide to proper bureaucratic conduct, upon what principles does a theory of bureaucratic responsibility rest? (3) What issues arise in putting responsibility into practice within a complex organizational setting? The article concludes that a democratic, process-based conception offers the most useful way of thinking about the responsibilities of bureaucratic officials. - Reproduced
Keywords: Democracy - United States; Public administration - United States; Civil service - United States; Bureaucracy - United States; Bureaucracy